Diabetes mellitus, hipertensi, obesitas dan usia berhubungan terhadap meningkatnnya risiko terjadinya disfungsi ereksi pada pasien benign prostat hyperplasia di rumah sakit sanglah bulan Juni sampai Oktober tahun 2015 - I Gusti Ayu Irma Vitriani; Gede Wirya Kusuma Duarsa (Universitas Udayana, 2018)
Benign Prostate Hyperplasia (BPH) is a degenerative disease that has complications of erectile dysfunction. Increased incidence of erectile dysfunction (ED) in cases of BPH is often accompanied by age risk factors as well as comorbid diseases such as diabetes mellitus, hypertension and obesity. This research uses cross-sectional study design. The technique of collecting samples by consecutive sampling method conducted in RSUP Sanglah Denpasar. The subjects were male patients with controlled BPH in Poly of Urology. The subjects were men who suffer Benign Prostate Hyperplasia (BPH) who visited the Poli Urology and treated at Sanglah Hospital. From this study showed that diabetes mellitus did not have a significant relationship to increase incident of ED in BPH, p=0.504. Hypertension has no significant relationship to increase incident of ED in BPH, p= 0.116. Obesity does not have a significant relationship to increase ED in BPH, p =0.058. While only age had a significant relationship to increase ED in BPH, p=0.016. The conclusion of the study is Diabetes Mellitus, Hypertension and Obesity not linked to increase incident of ED in BPH, while age has a close relationship to to increase incident of ED in BPH. Keywords: Benign Prostate Hyperplasia, ED, diabetes mellitus, hypertension, obesity, age